PRACTICAL PREREQUISITES FOR THE CERTIFICATE. - Olive, George S. (The Accounting Review, 1945)
The author has intentionally digressed from the limited subject of this article to emphasize the importance of the kind of experience any one should have who expects to do successful work in the office of a public accountant, and the author believes that the same situation holds as a requirement for taking the examination. It seems to him; therefore, that the existing situation is such that practicing accountants should realize the importance of this matter, if they are to attract to the profession the best of the material available. Of course, the aptitude tests now being developed by a special committee may be of great value to accountants in the selection of personnel, and the great advances made by the colleges in accounting pedagogy will result in much good. Results show that the essential ingredient is not theory, or book learning, but practical experience, and it seems logical to state that, if this profession is to maintain and to increase its prestige among the professions, its present members must see to it that those whom they would attract to the profession are properly trained in the practical aspects.